Cardiogenic shock complicating acute coronary syndromes - Abreu, G (2015)
INTRODUCTION: Despite advances in the treatment of patients with acute coronary syndromes (ACS), cardiogenic shock (CS) remains the leading cause of death in these patients. PURPOSE: Determine characteristics and management of patients with an ACS complicated by CS. Determine predictors of development of CS during hospitalization and predictors of in-hospital mortality. METHODS: Retrospective study of 2064 patients consecutively admitted for ACS in a Coronary Unit over a period of 4 years. RESULTS: During the years under study, 111 patients (5.4%) developed CS. Patients with CS were more likely to be older (69.8 ± 13.2 vs 63.5 ± 13.1 years, p<0.001); there were no significant differences in other clinical characteristics. Myocardial Infarction with ST segment elevation (STEMI) was more frequent in patients with CS (p<0.001). Patients with CS underwent less often coronary angiography (p<0.001), revascularization (p = 0.004) and were less treated with β-blocker (p <0.001) and ACE inhibitors therapy (p <0.001). In multivariate analysis, predictors of occurrence of CS during hospitalization were: tachycardia (OR 3.2, 95% CI 1.6-6.3), systolic blood pressure <100 mmHg (OR 4.1, 95% CI 2.1-8.0), GFR <60ml/min (OR 2.5, 95% CI 1.2-5.2), STEMI (OR 4.1, 95% CI 2.0-8.0) and Killip class > 1 (OR 3.5, 95% CI 1.8-6.8) at admission. The in-hospital mortality of patients with CS was 45%, compared with 1.7% in those who did not develop CS. Factors associated with an increased mortality in patients with CS included absence of coronary revascularization (OR 4.9, 95% CI 1.5-16.0), GFR <60ml/min (OR 4.4, 95% CI 1.3-15.6), advanced age (OR 6.4, 95% CI 1.6-26.2) and LVEF ≤ 35 % (OR 3.9, 95% CI 1.3-12.4). CONCLUSION: According to the literature, our review showed that CS in the context of ACS is associated with a high mortality. We identified clinical markers that are associated with the development of CS and may spot patients at risk earlier. Absence of coronary revascularization remains an independent predictor of mortality in CS.